Frequency dependent dielectric relaxation of Ba-doped BiFeO3 nanoparticles. (4th October 2019) - Suresh, Swathi; Kathirvel, A; Uma Maheswari, A; Sivakumar, M
Abstract: In this work, dielectric properties of barium doped bismuth ferrite (BFO) nanoparticles [Bi1-x Bax FeO3 ( x  = 0.005–0.025)] synthesized by hydrothermal method are investigated. X-ray diffractograms of pure and doped samples compared with rhombohedral R3c structure without the trace of any impurity phase. The average grain size of doped nanoparticles decreases with increase of Ba content. All the samples exhibited broad absorption in the region extending from 200–650 nm. The optical bandgap of doped samples reduces with an increase of Ba content and a significant reduction in bandgap is observed for 1.5% and 2.5% doping. Samples Bi1- x Ba x FeO3 ( x  = 0.0 and 0.015) exhibits anomalous dielectric response attributed to difference in frequency dependence relaxation of charge carriers within the grain and grain boundaries. The grain (Rg ) and grain boundary (Rgb ) resistances of these samples are evaluated by fitting the measured complex impedance data with an equivalent circuit. The dielectric constant of Bi1- x Ba x FeO3 ( x  = 0.015) is higher than that of pure BFO in the frequency range of 100 Hz–1 kHz. This is attributed to smaller grains and higher density of defects like oxygen vacancies leading to large space charge polarization. However, at higher frequencies (>1 kHz), the dielectric constant of pure BFO is higher than that of Bi1- x Ba x FeO3 ( x = 0.015) and hence high dielectric loss. Besides, 1.5% Ba doping has made the ions rigid, which shifts the relaxation peak of tan δ to lower frequency side and reduces the leakage current.